Socioeconomic impact of chronic delta hepatitis in Spain: Indirect costs of work absenteeism, presenteeism, and premature mortality - María Buti; Joaquín Cabezas; Raquel Domínguez-Hernández; Helena Cantero; Miguel Ángel Casado (PLoS ONE, 2025)
Introduction Patients with chronic delta hepatitis (CDH) exhibit higher levels of morbimortality than those with hepatitis B only, generating higher indirect costs for society. The aim of this study was to estimate the loss of productivity and costs resulting from work absenteeism and presenteeism as well as premature mortality among patients with CDH in Spain. Methods Patients with CDH in their working age (between 20–65 years) were estimated by an epidemiological flow model that incorporated the prevalence of infection with the hepatitis B and D viruses. To calculate the costs (year-2023) of absenteeism and presenteeism (over a time horizon of 1 year) as well as premature mortality (i.e., the period from death to expected retirement age), as measured in years of productive life lost (YPLL), the human capital method was used. Specific variables pertaining to the Spanish labour market (working population with hepatitis D virus (HDV), working days, average number of hours worked and gross annual salary) were considered for each sex and age group and distinguished based on infection status. All parameters were obtained from the literature and Spanish databases. Results A total of 1,313 CDH patients of working ages (59% men, 41% women) and 97 patients who performed unpaid housework were identified. A total of 300,113 working hours were lost per year (29,015 hours/absenteeism and 271,098 hours/presenteeism), which entailed total annual costs of €4.5M (€536,400/absenteeism and €3.9M/presenteeism) related to CDH. Among patients of working ages, CDH was estimated to cause 28 annual deaths at a cost of €8.2 M, resulting in 449 YPLL at an average cost of €18,297/YPLL. The indirect costs were estimated to be € 12.7M. Conclusions CDH entails significant economic burdens for society. Consideration of the indirect costs associated with CDH is crucial with respect to the design of public health policies and interventions.